DIETARY INTAKE TRENDS AMONG PREGNANT WOMEN IN RURAL AREA OF RAWALPINDI, PAKISTAN - Qureshi, Zubia; Khan, Rukhsana (Journal of Ayub Medical College Abbottabad, 2015)
Background: Adequate and healthy diet during pregnancy is essential for the health of both mother and new-born. This study was designed to know the health status of pregnant women and new-born by determining food taking habits of pregnant women. Methods: A cross sectional study was conducted on pregnant women of 2nd and 3rd trimester in a rural area of district Rawalpindi. Food frequency questionnaire and 24 hours dietary recall methods were used to identify their food consumption practices. Analysis was done by SPSS, while Nutrisurvey software was used to check the presence of Vitamin A, C, and Iron in specific fruits or vegetables. Results: A total of 110 pregnant women participated in the study. Most of them were illiterate, had low household income, and unemployed. Intake of meal frequency was according to the standards of Institute of Medicine (IOM), but food group consumption was not according to the recommendations of the United State Department of Agriculture (USDA). Most participants 102 (93.2%) knew that food is important during pregnancy. However an increase in frequency intake was observed in 63 (57.3%); while, 19 (17.3%) reported no change in food intake practices. About 67 (61%) were taking some sort of dietary supplements. Avoidance of any food 24 (22%), intake of additional food 51 (46%), craving 86 (78%), and aversion to any sort of food 42 (38%) was also identified in the study sample. No significant association was found between food group consumption, food availability and accessibility. Dietary diversity score, calculated according to the Food and Agriculture Organization (FAO) guidelines, indicated that about half study participants were not consuming adequate food. Conclusion: Study results show that food intake practices of pregnant women in the study area were not satisfactory. The results suggest that pregnant women need nutrition counselling regarding food intake practices during pregnancy.